Bright photo- and triboluminescence of centrosymmetric Eu(iii) and Tb(iii) complexes with phosphine oxides containing azaheterocycles. (16th July 2021) - Bryleva, Yuliya A.; Artem'ev, Alexander V.; Glinskaya, Ludmila A.; Rakhmanova, Mariana I.; Samsonenko, Denis G.; Komarov, Vladislav Yu.; Rogovoy, Maxim I.; Davydova, Maria P.
Abstract : Novel mononuclear Eu(iii ) and Tb(iii ) complexes based on phosphine oxides bearing pyridine, pyrimidine or pyrazine moieties show bright photo- and triboluminescence under ambient conditions. Abstract : Six centrosymmetric mononuclear Eu 3+ and Tb 3+ complexes of the type [LnL2 (hfac)3 ] have been synthesized employing diphenyl(pyridin-2-yl)phosphine oxide (Ph2 P(O)Py), diphenyl(pyridimin-2-yl)phosphine oxide (Ph2 P(O)Pym), and diphenyl(pyrazin-2-yl)phosphine oxide (Ph2 P(O)Pyr) as supporting ligands (L). The complexes [LnL2 (hfac)3 ] (L = Ph2 P(O)Py and Ph2 P(O)Pyr) comprise an eight-coordinate Ln 3+ ion with two monodentate O-donor phosphine oxides and three bidentate hfac − anions. In the [LnPh2 P(O)Pym2 (hfac)3 ] complexes, the Ln 3+ ion is nine-coordinated by three bidentate hfac − anions and two Ph2 P(O)Pym ligands, one of which is bound to Ln in a N, O-bidentate chelating mode, and the other acts as a monodentate O-donor ligand. The complexes display bright solid-state photoluminescence with emission quantum yields up to 56%. The integral intensity of 5 D0 → 7 F2 transition in the emission spectra of the Eu(iii ) complexes strongly depends on the coordination environment of the Eu 3+ ion. The asymmetric coordination geometry around Eu 3+ results in the large radiative rate constants. The crystals of the Eu(iii ) and Tb(iii ) complexes exhibit triboluminescence upon breaking under ambient conditions. The relationship between the triboluminescent properties and crystal structures of the complexes is discussed.